Improving Firm Value through Intellectual Capital, Good Corporate Governance and Financial Performance - Indriastuti, Maya; Kartika, Indri (Universitas Pendidikan Ganesha, 2021)
This study analyzed and tested empirically the firm value improvement through intellectual capital, good corporate governance, and financial performance. The samples of this study comprised 90 companies that analyzed by using the Structural Equation Model based on Partial Least Square with WrapPLS software. The results indicated that intellectual capital, good corporate governance, and financial performance were able to improve the firm value. The financial performance also was able to mediate the effect of intellectual capital and good corporate governance on firm value. The findings may become a consideration for regulators, especially the Financial Services Authority in making a a complete and strong regulation regarding the implementation of good corporate governance; as well as for investors to invest in companies listed on the Jakarta Islamic Index.